THE EFFECT OF QUALITY OF WORK LIFE AND JOB SATISFACTION ON PERFORMANCE MEDIATED KNOWLEDGE SHARING BY MSMEs EMPLOYEES - Sri Anggreani Magdalena Sitohang; Yohana Cahya Palupi Meilani (Feedforward: Journal of Human Resource, 2023)
This study aims to examine the effect of quality of work life and job satisfaction on employee performance mediated by knowledge sharing. The reason for doing this research is based on the existence of gap research which is strengthened by the results of an observational study which states the low performance of employees working in SME’s coffee shop in Depok. This study used 144 respondents to the actual study. Data were collected through a questionnaire using a Likert scale of 1–5. The data was obtained using a simple random sampling technique, where the data were taken at random without considering certain criteria. Data processing in this study uses the SmartPLS application, where the results show that the quality of work life significantly affect employee performance, job satisfaction significantly affects employee performance and knowledge sharing significantly affects employee performance. Knowledge sharing is able to mediate the effect of quality of work life and job satisfaction on employee performance.Bahasa Indonesia Abstrak: Penelitian ini bertujuan untuk meneliti terkait pengaruh quality of work life dan kepuasan kerja terhadap kinerja karyawan yang dimediasi oleh knowledge sharing. Alasan dilakukannya penelitian ini didasari atas adanya riset gap yang diperkuat dengan hasil studi observasi yang menyatakan rendahnya kinerja karyawan yang bekerja di UMKM coffee shop di Depok. Penelitian ini menggunakan 144 responden untuk studi aktual. Data dikumpulkan melalui kuesioner menggunakan skala likert 1–5. Data diperoleh menggunakan teknik simple random sampling, di mana data diambil secara acak tanpa mempertimbangkan kriteria-kriteria tertentu. Pengolahan data pada penelitian ini menggunakan aplikasi SmartPLS, di mana hasil menunjukkan bahwa quality of work life berpengaruh secara signifikan terhadap kinerja karyawan, kepuasan kerja berpengaruh secara signifikan terhadap kinerja karyawan dan knowledge sharing berpengaruh secara signifikan terhadap kinerja karyawan. Knowledge sharing mampu memediasi pengaruh quality of work life dan kepuasan kerja terhadap kinerja karyawan.